Conformational properties of DNA dodecamers containing four tandem repeats of the CNG triplets - Vorlícková, M; Zimulová, M; Kovanda, J; Fojtík, P; Kypr, J (Nucleic acids research, 1998)
We studied DNA dodecamers (CAG)4, (CCG)4, (CGG)4 and (CTG)4by CD spectroscopy and polyacrylamide gel electrophoresis. Each dodecamer adopted several ordered conformers which denatured in a cooperative way. Stability of the conformers depended on the dodecamer concentration, ionic strength, temperature and pH. The dodecamers, having a pyrimidine base in the triplet center, generated foldbacks at low ionic strength whose stem conformations were governed by the GC pairs. At high salt, (CCG)4 isomerized into a peculiar association of two strands. The association was also promoted by high oligonucleotide concentrations. No similar behavior was exhibited by (CTG)4. At low salt, (CGG)4 coexisted in two bimolecular conformers whose populations were strongly dependent on the ionic strength. In addition, (CGG)4 associated into a tetraplex at acidic pH. A tetraplex was even observed at neutral pH if the (CGG)4 concentration was sufficiently high. (CAG)4 was very stable in a monomolecular conformer similar to the known extremely stable foldback of the (GCGAAGC) heptamer. Nevertheless, even this very stable conformer disappeared if (CTG)4 was added to the solution of (CAG)4. Association of the complementary strands was also strongly preferred to the particular strand conformations by the other couple, (CCG)4 and (CGG)4.
Keywords: osmolární koncentrace; Sodium Chloride; konformace nukleové kyseliny; chlorid sodný; Nucleic Acid Conformation; Electrophoresis, Polyacrylamide Gel; Osmolar Concentration; trinukleotidové repetice; elektroforéza v polyakrylamidovém gelu; Trinucleotide Repeats; cirkulární dichroismus; Circular Dichroism